Hygienic Assessment of The Condition of The Oral Mucosa After Orthopedic Treatment - Islamova Nilufar Bustanovna; Turdiyev Jakhongir Avazbek ugli (Scientific Trends, 2024)
The most common causes of complications in the mouth and the unsuitability of fixed structures are considered to be inflammatory processes, caries and its complications (16,4–25,2 %) [7,8,12], thermal burns of the pulp (4.3%) [4,6,9], cementation of the supporting crowns (8-21% of all complications). These processes often develop in the area of the edge of artificial crowns and are caused by the destruction of the cement layer that fixes the non-removable prosthesis. One of the typical complications of dental prosthetics, which often develops within the first year after fixation of the artificial crown, is the exposure of the neck of the tooth root due to gum recession [3,5,11]. The occurrence of cervical or secondary caries under an artificial crown was noted in 1.78% of cases. This is above the average level of foreign ones (0.4%), but falls within the range of the given parameters (0-2.7%). The need for endodontic treatment is 4.63% [2,7,13], in foreign literature (0-6%) [1,3,14]. Papillitis, gingivitis and marginal periodontitis occurred in 1.07% of cases, in foreign researchers — 0.6%. In the long term, up to 5 years, the average parameters of the lesion of the marginal periodontium leveled out and amounted to 16.96%. Deep cracks, as well as chipping, and broken cladding were noted in 5.22% of cases [2,8,14]. In the dental practice of the world, there is a high frequency of various orthopedic and orthodontic defects, including forms manifested in the form of various degrees of adentia. The prevalence of adentia has increased significantly and according to the data is 35.4-62.9% [5,8.10]. Despite significant advances in the field of materials science and improvement of the quality of dental prostheses, various authors note complaints of intolerance in patients from 0.6 to 12% [1,8,11]. Many researchers note that patients with removable dentures have different levels of adaptive capabilities, the study of which makes it possible to predict the development of intolerance. When diagnosing and predicting intolerance to dentures, it will allow obtaining objective information about compensatory and adaptive reactions occurring during the use of removable dentures and developing preventive measures to accelerate the adaptive capabilities of the body [3,6,10]. Thus, there is a need to form a concept that makes it possible to offer modern methods of diagnosis, prevention and treatment of adentia, which have properties of action on oral homeostasis and the general condition of the body.